Ethnicity and epistemological-enhanced instruction effects on beliefs, thinking skills and concept understanding in chemistry - Filoteo, Lourdes Bolo (2009)
The prevalent epistemological beliefs of students in chemistry were assessed in this study through their mean scores using the researcher-made test. It also determined the effectiveness of the epistemological-enhanced instruction (EEI) against the lecture method of instruction (LMI). The instruments used were the Epistemological Beliefs in Chemistry Questionnaire, Watson-Glaser Critical Thinking Appraisal, Conceptual Understanding Test, Student Background Information Questionnaire and Interview Guide. Findings showed that the epistemological beliefs prevalent among nursing students were sophisticated, theoretical, empirical and perceptual beliefs in the nature of chemistry knowledge. Students exposed to the EEI have a posttest mean score that is significantly higher than those exposed to LMI in the epistemological beliefs scale.
Thesis (Ph.D. Chemistry Education)--University of the Philippines, Diliman.
Best dissertation.
Keywords: Chemistry -- Study and teaching (Higher) -- Philippines -- Zamboanga City (Zamboanga del Sur); Critical thinking -- Philippines -- Zamboanga City (Zamboanga del Sur); Nursing students -- Philippines -- Zamboanga City (Zamboanga del Sur); College freshmen -- Philippines -- Zamboanga City (Zamboanga del Sur)